Trends in indications, complications and outcomes for venous resection during pancreatoduodenectomy. Issue 11 (17th August 2017) - Kleive, D; Sahakyan, M A; Berstad, A E; Verbeke, C S; Gladhaug, I P; Edwin, B; Fosby, B; Line, P-D; Labori, K J
Abstract: Background: Pancreatoduodenectomy with superior mesenteric–portal vein resection has become a common procedure in pancreatic surgery. The aim of this study was to compare standard pancreatoduodenectomy with pancreatoduodenectomy plus venous resection at a high-volume centre, and to examine trends in management and outcome over a decade for the latter procedure. Methods: This retrospective observational study included all patients undergoing pancreatoduodenectomy with or without venous resection at Oslo University Hospital between January 2006 and December 2015. Trends were evaluated by assessing preoperative clinical and radiological characteristics, as well as perioperative outcomes in three time intervals (early, intermediate and late). Results: A total of 784 patients had a pancreatoduodenectomy, of whom 127 (16·2 per cent) underwent venous resection. Venous resection resulted in a longer operating time (median 422 versus 312 min; P = 0·001) and greater estimated blood loss (EBL) (median 700 versus 500 ml; P = 0·004) than standard pancreatoduodenectomy. The rate of severe complications was significantly higher for pancreatoduodenectomy with venous resection (37·0 versus 26·3 per cent; P = 0·014). The overall burden of complications, evaluated using the Comprehensive Complication Index (CCI), did not differ (median score 8·7 versus 8·7; P = 0·175). Trends in venous resection over time showed a significant reduction in EBL (median 1050 versus 375 ml; P = 0·001) and duration of hospital stay (median 14 versus 9 days; P = 0·011) between the early and late periods. However, despite an improvement in the intermediate period, severe complication rates returned to baseline in the late period (18 of 43 versus 9 of 42 versus 20 of 42 patients in early, intermediate and late periods respectively; P = 0·032), as did CCI scores (median 20·9 versus 0 versus 20·9; P = 0·041). Conclusion: Despite an initial improvement in severe complications for venous resection during pancreatoduodenectomy, this was not maintained over time. Every fourth patient with venous resection needed relaparotomy, most frequently for bleeding. Abstract : Severe complications, more reoperations